How to write a paper - Hall, George M. (George Martin) (Chichester, West Sussex : Wiley-Blackwell, 2013)
"This concise paperback is about writing a paper for publication in biomedical journals. Its straightforward format - a chapter covering ea ch of part of the structured abstract - makes it relevant and easy to u se for any novice paper writer.How to Write a Paper addresses the mecha nics of submission, including electronic submission, and how publishers handle papers, writing letters to journals abstracts for scientific me etings, and assessing papers. This new edition also covers how to write a book review and updated chapters on ethics, electronic publication a nd submission, and the movement for open access"--
Machine generated contents note: Preface to Fourth Edition Preface t o Fifth Edition 1. Structure of a scientific paper George M. Hall 2. In troductions Richard Smith 3. Methods Gordon B. Drummond 4. Results Char les W. Hogue 5. Discussion George M. Hall 6. Titles, abstracts and auth ors Kevin W. Eva 7. Who should be an Author? Richard Horton 8. Referenc es Simon Howell and Liz Neilly 9. Electronic submissions Michael Willis 10. Open Access Mark Ware 11. How to write a letter Michael Doherty 12 . How to prepare an abstract for a scientific meeting Robert N. Allan 1 3. How to write a case report Martin Neil Rossor 14. How to write a rev iew Paul Glasziou 15. How to write a book review Mark W. Davies and Luk e A. Jardine 16. The role of manuscript assessor Domhnall MacAuley 17. The role of editor Jennifer M. Hunter 18. What a publisher does Gavin S harrock and Elizabeth Whelan 19. Style: what it is and why it matters S haron Leng 20. Ethics of publication Chris Graf and Elissa Wilson Index .
Includes bibliographical references and index.
Keywords: Medical writing; Writing; Publishing